Size-dependent exciton dynamics in one-dimensional perylene bisimide aggregates - Steffen Wolter; Janis Aizezers; Franziska Fennel; Marcus Seidel; Frank Würthner; Oliver Kühn; Stefan Lochbrunner (New Journal of Physics, 2012)
The size-dependent exciton dynamics of one-dimensional aggregates of substituted perylene bisimides are studied by ultrafast transient absorption spectroscopy and kinetic Monte-Carlo simulations as a function of the excitation density and the temperature in the range of 25–90 °C. For low temperatures, the aggregates can be treated as infinite chains and the dynamics is dominated by diffusion-driven exciton–exciton annihilation. With increasing temperature the aggregates dissociate into small fragments consisting of very few monomers. This scenario is also supported by the time-dependent anisotropy deduced from polarization-dependent experiments.